2013
DOI: 10.1088/1741-2560/10/4/045002
|View full text |Cite
|
Sign up to set email alerts
|

3D Parylene sheath neural probe for chronic recordings

Abstract: The provided electrophysiological and immunohistochemical data provide strong support to the viability of the developed probe technology. Furthermore, the obtained data provide insights into further optimization of the probe design, including tip geometry, use of neurotrophic and anti-inflammatory drugs in the Matrigel coating, and placement of the recording sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 59 publications
(65 reference statements)
3
150
3
1
Order By: Relevance
“…And for the smallest chronically implantable extracellular microelectrode so far reported — an electrode with a 15 µm 2 cross-sectional area 173 — two-photon imaging surrounding the implant revealed a lack of astrogliosis and minimal disruption of the vasculature. However, reduced stiffness can make softer 156,174 and subcellular devices 48,68,175 difficult to implant, requiring the use of an insertion tool 175,176 or dissolvable shuttle 177,178 . Since new device designs often employ both softer materials and reduced feature sizes, the relative impact of each of these factors on the tissue response can be difficult to interpret.…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…And for the smallest chronically implantable extracellular microelectrode so far reported — an electrode with a 15 µm 2 cross-sectional area 173 — two-photon imaging surrounding the implant revealed a lack of astrogliosis and minimal disruption of the vasculature. However, reduced stiffness can make softer 156,174 and subcellular devices 48,68,175 difficult to implant, requiring the use of an insertion tool 175,176 or dissolvable shuttle 177,178 . Since new device designs often employ both softer materials and reduced feature sizes, the relative impact of each of these factors on the tissue response can be difficult to interpret.…”
Section: Glial-activation Challenges and Design Considerationsmentioning
confidence: 99%
“…Although this increase does not affect the functionality of these thermoformed implantable devices [33], the thermoforming process has demonstrated these changes to the sensitive electrode surface that can be explained by a smoothing of the electrode surface during annealing [46] as well as possible mobilized chlorine adsorption on the surface during annealing [50,51] observed in literature. Additional work is underway in ascertaining the source of these changes.…”
Section: Electrochemical Effectsmentioning
confidence: 70%
“…Histological studies (Biran et al, 2007;Kim et al, 2004) report that the strain induced immune response, caused by the rigid tethering of the electrode to the skull, leads to an increase in microglial activity in the implanted tissue as compared to untethered electrodes (Gilletti and Muthuswamy, 2006). Quantitative studies have shown that electrode with low Young's modulus material or redefined geometry for high compliance can provide front-end strain relief and polymers such as polyimide and Parylene-C, with their good biocompatibility, have been the choice of researchers for electrode substrate materials (Sankar et al, 2013;Seymour et al, 2011;Ziegler Contents Kim, 2013;Rodger et al, 2008;Metallo et al, 2011). Furthermore it is well known that the miniaturization of the electrode size is a critical requirement for single neuron recording and for electrical stimulation restricted to small populations of neuronal elements.…”
Section: Introductionmentioning
confidence: 99%